Into the wild : yet another misadventure - Cronin, Doreen (Cronin, Doreen. Chicken Squad, 2016)
The fluffy, fearless Chicken Squad detectives are determined to find out who the new addition is in their yard, so, equipped with the latest surveillance gear, the chicks venture into the wild to get answers.